Unveiling wheat growth promotion potential of phosphate solubilizing Pantoea agglomerans PS1 and PS2 through genomic, physiological, and metagenomic characterizations - Sharma, Pinki; Pandey, Rajesh; Chauhan, Nar Singh (Frontiers in Microbiology, 2024)
Phosphorus is an abundant element in the earth's crust and is generally found as complex insoluble conjugates. Plants can not assimilate insoluble phosphorus and require external supplementation as chemical fertilizers to achieve a good yield. Continuous use of fertilizers has impacted soil ecology, and a sustainable solution is needed to meet plant elemental requirements. Phosphate solubilizing microbes could enhance phosphorus bioavailability for better crop production and can be employed to attain sustainable agriculture practices. The current study aimed to tap the biofertilizer potential of rhizosphere microbiota towards this. Culture-dependent exploration identified phosphate-solubilizing PS1 and PS2 strains from the wheat rhizosphere. These isolates were rod-shaped, gram-negative, facultative anaerobic bacteria, having optimum growth at 37°C and pH 7. Phylogenetic and phylogenomic characterization revealed their taxonomic affiliation as Pantoea agglomerans subspecies PS1 & PS2. Both isolates exhibited good tolerance against saline (>10% NaCl (w/v), >11.0% KCl (w/v), and >6.0% LiCl (w/v)), oxidizing (>5.9% H2O2 (v/v)) conditions. PS1 and PS2 genomes harbor gene clusters for biofertilization features, root colonization, and stress tolerance. PS1 and PS2 showed nitrate reduction, phosphate solubilization, auxin production, and carbohydrate utilization properties. Treatment of seeds with PS1 and PS2 significantly enhanced seed germination percentage (P=0.028 and P=0.008, respectively), number of tillers (P=0.0018), number of leaves (P=0.0001), number of spikes (P=0.0001) and grain production (P=0.0001). Wheat rhizosphere microbiota characterizations indicated stable colonization of PS1 and PS2 strains in treated seeds at different feek stages. Pretreatment of seeds with both strains engineered the wheat rhizosphere microbiota by recruiting plant growth-promoting microbial groups. In vitro, In vivo, and microbiota characterization studies indicated the biofertilizer potential of Pantoea sp. PS1 & PS2 to enhance wheat crop production. The employment of these strains could fulfill plant nutrient requirements and be a substitute for chemical fertilizers for sustainable agriculture.